New anticoagulants - promising and failed developments - Harenberg, Job; Hetjens, Svetlana; Krejczy, Martin; Wehling, Martin (British journal of pharmacology, 2012)
New direct and indirect acting factor Xa (FXa) and thrombin inhibitors are being developed to overcome the downsides of the conventional anticoagulants - unfractionated and low molecular weight heparins and vitamin K antagonists. Ximelagatran and idraparinux failed to demonstrate an acceptable safety profile. Rivaroxaban and dabigatran are approved for the post-operative prevention of thromboembolic complications after elective hip or knee replacement surgery; dabigatran is approved for the prevention of embolism in patients with atrial fibrillation in an increasing number of countries. Several novel indirect antithrombin-dependent anticoagulants as well as antithrombin-independent oral direct FXa and thrombin inhibitors are investigated in multiple indications for the prophylaxis and treatment of venous thromboembolism and the prophylaxis of arterial thrombotic disorders. Quality-adjusted life years costs and incremental cost-effectiveness ratios are relatively high at present, but may decrease after approval of more new anticoagulants for additional indications.